Estrus synchronization and fixed time artificial insemination (FTAI) in dairy buffaloes during seasonal anestrus - Frares, Luciana Ferri; Weiss, Romildo Romualdo; Kozicki, Luiz Ernandes; Santangelo, Renata Prestes; de Abreu, Renata Azevedo; do Santos, Ivo Walter; Dell'aqua Junior, José Antônio [UNESP]; Breda, José Carlos (FapUNIFESP (SciELO), 2013)
The aim of this work was to study estrus synchronization and fixed time artificial insemination (FTAI) in dairy buffaloes during season anestrus. One hundred thirty-nine dairy buffaloes in seasonal anestrus were divided in two groups as G1(n=66) and G2(n=73). The protocols for both the groups were the same until day (D)14:D0 administration of 2.0 mg estradiol benzoate and implantation of progesterone device (P4) for 14 days; D14 removal of P4 plus 150 mg of cloprostenol and 400 IU of equine chorionic gonadotropin. On D16, G1 received 10 mg of buserelin and G2 100 mg deslorelin acetate. On D17, both the groups were submitted to FTAI. Ultrasonographic examinations of ovaries were performed on D0, D14, D16 and D17. Results showed that pregnancy rates in G1 and G2 were 20 and 41% (p<0.05) and the ovulation rates were 16.6 and 37%, respectively (p<0.05). The dominant follicle (DF) diameter on D16 was 7.9 mm in G1 and 8.9 mm in G2 (p>0.05). Thirty-five percent of the animals in G1 and 54.1% in G2 showed a diameter DF greater than 8.0 mm on D16 (p>0.05). Thus, it could be concluded that the protocols synchronized the estrus, leading the concentration of the parturitions in the period of low milk production. Deslorelin was more efficient than buserelin due the higher percentage of DF ovulation and higher pregnancy rates.
Keywords: Buserelin; Dairy buffaloes; Deslorelin; Estrus synchronization; FTAI; Seasonal anestrus